Optimisation of fermentation conditions for the production of gamma-aminobutyric acid (GABA)-rich soy sauce - Shin Yee, Chong; Ilham, Zul; Cheng, Acga; Abd Rahim, Muhamad Hafiz; Azhari, SitiHajar; Yuswan, Mohd Hafis; Mohd Zaini, Nurul Aqilah; Reale, Anna; Di Renzo, Tiziana; Wan-Mohtar, Wan Abd Al Qadr Imad (Elsevier, 2024)
This study addresses the challenge of enhancing gamma-aminobutyric acid (GABA) content in soy sauce through optimized fermentation condition. Using a multiple starter culture, consisting of Aspergillus oryzae strain NSK, Bacillus cereus strain KBC and Tetragenococcus halophilus strain KBC, the incubation conditions including the percentage of bacterial inoculum (10, 15 and 20 %), pH (3, 5 and 7) and agitation speed (100, 150 and 200 rpm) were optimized through Response Surface Methodology (RSM). Under the optimal conditions (20 % inoculum, pH 7 and stirring at 100 rpm), the multiple starter culture generated 128.69 mg/L of GABA after 7 days and produced 239.08 mg/L of GABA after 4 weeks of fermentation, which is 36 % higher than under non-optimized conditions (153.48 mg/L). Furthermore, sensory analysis revealed high consumer acceptance of the fermented soy sauce than the control (soy sauce without any treatment and additional bacteria) and commercial soy sauce. Consumers indicated that the starter culture offered an improved umami taste and reduced bitter, sour and salty flavours compared to the commercial product. Under optimal fermentation conditions determined by RSM statistical analysis, the multiple starter culture is able to produce high levels of GABA and is more likely to be accepted by consumers. The findings of this research have the potential to impact the food sector by offering a functional soy sauce with added health benefits and also being well-received by consumers.